Evaluation of an implemented quality management system (QMS) at one of the South African government departments: employee perceptions of the effect of the QMS intervention - Maluleke, Yinywane Leon (Rhodes University, Faculty of Commerce, Investec Business School, 2009)
This study is about the employee perceptions of the effect of the Quality Management System intervention that was implemented at one of South Africa's government departments. This organisation's Quality Management System being one of the first in the government or public sector in South Africa to be implemented, creates the possibility for this Quality Management System model to be used to develop Quality Management Systems in other departments or organisations belonging to the government or the public sector in South Africa and the Southern African region. According to Madu & Kuei (1995), Quality Management System describes a situation where all business functions are involved in a process of continuous quality improvement. This implies that the development and implementation of Quality Management Systems in government departments and the public sector will improve the quality of services delivery. The findings of this study indicated that a Quality Management System can be used to improve the level of service delivery in the public sector. The Quality Management System should be planned developed and implemented over a period of time in five phases (i) Phase 1 - Determination of the scope of Quality Management System implementation (ii) Phase 2 "“ Training (iii) Phase 3 "“ Development of Procedures (iv) Phase 4 "“ Pilot implementation of procedures (v) Phase 5 "“ Evaluation of Quality Management System and rollout. It usually takes three or more years to establish an organisation-wide Quality Management System, although technical improvement to the workflow can be as quickly as six to eight months. And finally, for the Quality Management System to be developed, implemented and maintained successfully, Maximisation of Performance objectives, Good Leadership, Motivation of staff, Implementation of Change Management, Employee Involvement, Long-term Top Management Commitment, Provision of Training, Introduction of Quality Improvement Projects, Measuring Quality Management System Progress and Reward Accomplishment, are the fundamental concepts or principles that should be considered.
Keywords: Total quality management in government; Public administration -- South Africa